Shadow wave - Muchamore, Robert (Great Britain: Hodder Children's Book, 2010)
After a tsunami causes massive devastation to a tropical island, its governor sends in the bulldozers to knock down villages, replacing them with luxury hotels. Guarding the governor's family isn't James Adams' idea of the perfect mission-- and then retired agent Kyle Blueman comes up with an unofficial and highly dangerous plan of his own. James must choose between loyalty to CHERUB, and loyalty to his friend.
"Originally published in Great Britain in 2010 by Hodder Children's Books"--Title page verso.
Ages 12 up.
Keywords: Great Britain. -- MI5; Intelligence service -- Great Britain -- Juvenile fiction; Spy stories; Young adult fiction; Loyalty -- Fiction; Political corruption -- Fiction; Spies -- Fiction; Adventure and adventurers -- Fiction; Intelligence service; Spy stories; Young adult fiction; Great Britain -- Fiction; Great Britain; Action and adventure fiction; Fiction; Spy stories; Suspense fiction; Spy fiction; Action and adventure fiction